Characterization of Turkish honeybee pollens by principal component analysis based on their individual organic acids, sugars, minerals, and antioxidant activities. (October 2017) - Kalaycıoğlu, Zeynep; Kaygusuz, Hakan; Döker, Serhat; Kolaylı, Sevgi; Erim, F.Bedia
Abstract: The purpose of this study was to characterize the Anatolian honey-bee collected pollens according to their sugar, organic acid, mineral, total phenolic contents, and antioxidant activities. Individual organic acids and sugar contents of pollens were determined by capillary electrophoresis. Fructose (F) and glucose (G) were the major sugars. Bee pollen samples contained very diverse organic acids. Gluconic acid was the major organic acid (5.9–32 g/kg) in all the pollen samples. The second highest organic acid content belonged to lactic acid, ranging from 0.72 to 1.2 g/kg. Fourteen elements were determined in each pollen sample by inductively coupled plasma-mass spectrometry (ICP-MS). The Folin-Ciocalteu method was applied for the total phenolic contents of the pollens. The antioxidant activities were evaluated using 1, 1-diphenyl-2-picryl-hydrazil (DPPH) radical scavenging activity. Principal component analysis (PCA) was applied to analyze results in order to classify the bee pollens from different botanical origins and regions. Highlights: Minerals, organic acids, sugars, and antioxidant activities of pollens were tested. Constituents of 10 pollen samples from Turkey were evaluated according to PCA. Acetic acid and Ca contents were found significantly higher in buckwheat pollen. Na, K, and Ca are dominant minerals in all pollen samples.